STUDY OF SQUID INK WASTE UTILIZATION AS A WET NOODLE NATURAL DYES WITH DIFFERENT MATTER BINDING ON CONSUMER ACCEPTANCE - Dian Monica Hutasoir; Syahrul '; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purpose of this research is to utilize waste utilization as a wet noodle natural dyes with different matter binding on consumer acceptance. Design used in this study was completely randomized design (CRD) factorial, with two treatments that wheat flour (B1) and corn starch (B2) and the concentration of squid of ink. The parameters observed are organoleptic test and proximate test (moisture content, protein content, fat content, ash content, and carbohydrate content). The result of study showed that wheat flour with added squid of ink to value organoleptic appearance, aroma,taste and value proximate moisture content, protein content, fat content, ash content, and carbohydrate content. Based on the level of consumer acceptance panelists preferred wet noodles are wheat flour with the addition of squid of ink 1.5%, where the value of such a (3.07%) shiny; aroma (2.80%) is not the typical smell of a wet noodle wheat flour; texture (3.07%) is very compact with a water content (46.82%); protein content (30.11%); fat content (1.89%); and total bacterial colony (3.73 x 104).Keywords:wet noodle, wheat flour, corn starch, fish protein concentrate, squid of ink